The Process of Creating Mundong Dance in Sukoharjo Regency - Agnes Aprilia Rahayu; Widodo Broto Sejati; Indriyanto Indriyanto (Jurnal Seni Tari, 2023)
Mundong Dance is a new dance creation created by Christina Sri Asih Handayani in 2011 in Sukoharjo. She got inspiration from the typical product of the people of the Sukoharjo Regency, namely traditional herbal medicine (jamu). The creation of the mundong dance is because the choreographer hoped that there would be a unique art from Sukoharjo, and it could become an excellent dance for the Sukoharjo Regency. This research used the theory of creation from Alma Hawkins, translated by Sumandiyo Hadi. This study aims to describe the process of creating mundong dance in the Sukoharjo Regency. This study used a choreographic approach with qualitative-descriptive research methods. Data collection techniques used are observation, interviews, and documentation. The data analysis used is data collection, data reduction, data presentation, and conclusions. The results of this study show that the creation process of the mundong dance is obtained from the idea of working. It is because of the absence of dance describing the uniqueness and identity of the Sukoharjo Regency, namely jamu gendong. It is poured in three stages of creation, namely exploration producing movements of ngramu empon-empon, ngedoli jamu, and mundur beksan, improvisation creating a movement of manembah, and composition combining all of the movement findings in the process of exploration and improvisation. The elements of dance choreography in the creating mundong dance consist of movements, music, makeup, fashions, properties, floor patterns, and dancers.